NEW GEOCHEMICAL DATA ON UPPER DEVONIAN THOLEIITIC BASALTS OF THE VORONEZH ANTECLISE - Lyapunov S.M.; Yermolayev B.V.; Gladkikh V.S. (My University, 1987)
The basalts investigated were penetrated in drillholes near the villages of Nizhniy Mamon and Podkolodnovka as three flows with an overall thickness of 3 to 57 m. An earlier study of mineral and chemical compositions of least altered varieties of these rocks showed that the are tholeiites with normative hypersthene (13 to 20 percent) and quartz (1 to 3.7). In niobium, zirconium and nickel content, these tholeiites are similar to those of cratons like the Karroo. To determine the petrographic association of such basalts, the authors investigated the distribution of rare-earth elements (REE), Hf, Th, Ba and Sr and, once more, of Nb, Ta, Zr, Sc, Co and Cr by neutron-activation and X-ray fluorescence analysis. Study results are discussed.
Keywords: Devonian; Paleozoic::Devonian; Палеозой::Девонская